2010
DOI: 10.1097/dad.0b013e3181ca4a13
|View full text |Cite
|
Sign up to set email alerts
|

Intraoral Morgellons Disease or Delusional Parasitosis: A First Case Report

Abstract: Morgellons disease is a new emerging disease that is still controversial and believed to be, by some practitioners, as nothing more than delusional parasitosis. The Center for Disease Control has recently launched an epidemiological investigation into this disease due to the increased number of reports. A first case is reported of an oral lesion and symptoms consistent with Morgellons disease. The nature of the characteristic fibers associated with the intraoral lesion is investigated. Research has started at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 8 publications
1
9
0
Order By: Relevance
“…There are only three case studies that specifically mention the presence of fibers either projecting from or embedded in skin. 57 , 72 , 75 Roncati et al 72 reported “grayish spots” under skin, then used scanning electron microscopy (SEM) and energy-dispersive spectroscopy (EDS) to study the spots. SEM showed that the spots were associated with fibers described as “synthetic wire” consistent with samples from a washing machine, as well as keratin fibers consistent with hair from the patient’s dog.…”
Section: Evidence Supporting the Hypothesis Of Dpmentioning
confidence: 99%
See 1 more Smart Citation
“…There are only three case studies that specifically mention the presence of fibers either projecting from or embedded in skin. 57 , 72 , 75 Roncati et al 72 reported “grayish spots” under skin, then used scanning electron microscopy (SEM) and energy-dispersive spectroscopy (EDS) to study the spots. SEM showed that the spots were associated with fibers described as “synthetic wire” consistent with samples from a washing machine, as well as keratin fibers consistent with hair from the patient’s dog.…”
Section: Evidence Supporting the Hypothesis Of Dpmentioning
confidence: 99%
“…Dovigi provided convincing evidence that the fibers extracted from an oral lesion on the mucosal distal tuberosity of a tooth were synthetic carbon-based fibers, but there is no evidence that the fibers were self-implanted. 57 Dental floss is composed of synthetic fibers, such as nylon. 78 Fibers could have been introduced during flossing, especially if the floss had frayed and become lodged between teeth, eventually festering and causing a lesion.…”
Section: Evidence Supporting the Hypothesis Of Dpmentioning
confidence: 99%
“…Two rare oral occurrences have been also reported in literature [3,4]. The term "Morgellons" was used for the first time around the year 1600 in a letter written by Sir Thomas Browne (1605-1682), in which he described an endemic condition among the little children in Languedoc, called the Morgellons, concerning with a "hair growth" on the back of the body, combined with convulsions and coughing [5].…”
mentioning
confidence: 99%
“…The administration of sulpiride, atypical antipsychotic, resulted in complete resolution of her oral symptoms [ 18 ]. Another case, being reported in 2010, when a 61-year-old Caucasian female presented to her periodontist with oral lesions for a duration of 2 years and a complaint of “numerous fibers” emerging from her oral lesion with itching and irritation from the lesion [ 19 ]. Pathological examination of these fibers revealed nothing, but synthetic fibers that were possibly implanted into the oral mucosa by the patient [ 19 ].…”
Section: Discussionmentioning
confidence: 99%